A noética de Avicena no Kitab al-nafs: como pensamento e intuição se combinam no ato de conhecer - Meline Costa Sousa (2013)
Having in mind the disagreement between contemporary commentators on the way by which theoretical intellect knows from Avicena's Kitb al -nafs, I investigate if this activity is performed through an internal sense that helped by the intellect to abstract the material form or if it is a proper activity of the intellect that does not depend on material forms, but only intuiting the intelligible forms. However, some passages of V.5 and 6, where Avicenna describes the conjoint activity of intellect and internal senses and its proper activity conduce to the conclusion that two elements are necessary to the knowledge: unifying the multiplying the unity; in others words, it is not enough that the intellect apprehends the simple universal, but it also needs to intuit the middle term of the syllogism.